A comparison of the five-minute cognitive test with the mini-mental state examination in the elderly for cognitive impairment screening - Pan, Xiaoli; Cheng, Xiaoqin; Zhang, Jie; Xia, Yingfeng; Zhong, Chunjiu; Fei, Guoqiang (Frontiers in Neuroscience, 2023)
The five-minute cognitive test (FCT) is a novel cognitive screening method with the quick and reliable merit for detecting cognitive impairment at an early stage. The diagnostic power of FCT in differentiating subjects with cognitive impairment from people with cognition in a normal range was demonstrated effective as that of the Mini-Mental Status Evaluation (MMSE)in a previous cohort study. Here, we analyzed the effect of sociodemographic and health-related factors on FCT performance and further investigated the consistency of FCT. Then, we compared the correlation of subitem scores of FCT or MMSE with a comprehensive battery of neuropsychological tests that focus on specific domains of cognition. Finally, the association of the total FCT scores with brain subregion volumes was investigated. There were 360 subjects aged 60 years or above enrolled in this study, including 226 adults with cognitive abilities in normal range, 107 subjects with mild cognitive impairment (MCI) and 27 mild Alzheimer’s disease (AD). The results showed that the total FCT scores was negatively associated with increasing age (β=-0.146, P<0.001), and positively associated with education attainment (β= 0.318, P<0.001), dwelling condition with family (β=0.153, P<0.001) and the Body Mass Index (β=1.519, P<0.01). The internal consistency of the FCT (Cronbach’s α) was 0.644. The sub-scores of FCT showed a significant correlation with other specific neuropsychological tests. Impressively, the total FCT scores showed a significantly positive association with the volumes of hippocampus related subregions (r=0.523, P<0.001) and amygdala (r=0.479, P<0.001), but not with cerebellum (r=0.158, P>0.05) or subcortical subregions (r=0.070, P>0.05). Combining with previous data, FCT is a reliable and valid cognitive screening test for detecting cognitive impairment in a community setting.